ISOLASI DAN IDENTIFIKASI SENYAWA AKTIF STIMULATOR PROLIFERASI SEL LIMFOSIT DARI UMBI SARANG SEMUT (Myrmecodia tuberosa (non Jack) Bl.) - , AKHMAD KHUMAIDI; , Prof. Dr. Ediati Sasmito, SE., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Ant plant (Myrmecodia tuberosa (non Jack) Bl.) has been used traditionally to treat various diseases such as diarrhea, hemorrhoids, brain cancer, and cervical cancer. Previous research has reported the potency of ethyl acetate fraction to increase lymphocytes proliferation. The aim of this study was to determine the active chemical compound responsible for the healing effects associated with immune response and to evaluate whether the total flavonoid and total phenolic contents correlated to the activity. Separation of ethyl acetate was done by vacuum liquid chromatography (VLC) with a polarity gradient system starting from n-hexane, a mixture of n-hexane-ethyl acetate, ethyl acetate 100 %, a mixture of ethyl acetate-methanol and methanol 100 %. Subfraction effect on lymphocytes proliferation was examined on BALB/c mice lymphocytes by an in vitro technique using MTT method. Total flavonoid content was determined by using spectrophotometry with AlCl3 method and was calculated as percent quercetine equivalent (% QE). Total phenolic content was determined by Folin-Ciocalteu method and calculated as percent gallic acid equivalent (% GAE). Active subfraction was hydrolyzed by refluxing in HCl 2% for 1 hour. Afterwards the result was further fractionated using preparative thin layer chromatography. Vacuum liquid chromatography fraction yielded five subfractions with total recovery of 81.78 %. Subfraction V was the most active subfraction. Total flavonoid content contributed to lymphocyte proliferation activity by 60.6% and total phenolic by 16.7%. Active compound was identified by using TLC, UV-Vis and 1H-NMR as an aglycone of isoflavon derivate.